Do Gender Differences in Depression Remain after Controlling for Early Maladaptive Schemas? An Examination in a Sample of Opioid Dependent Treatment Seeking Adults - Shorey, Ryan C. (2012)
The abuse of opioids is a serious and prevalent problem and research is needed on factors that may place individuals at risk for misusing opioids. Depression is a common co-morbid mental health problem among opioid users. Theory and research suggests that early maladaptive schemas may underlie mental health problems including depression and substance abuse. The current study sought to determine whether early maladaptive schemas were associated with depression among a treatment seeking sample of male and female opioid users (N = 194). We also examined whether depression, as assessed by the MMPI-2, varied by gender and whether gender differences in depression remained after controlling for early maladaptive schemas. Results showed that females scored significantly higher than males on 3 of the 5 early maladaptive schema domains, and that gender did not predict depression after controlling for schema domains. Early maladaptive schemas were also more strongly associated with depression for men than women. Implications of these findings for interventions and future research are discussed.